Response of runoff and nitrogen loadings to climate and land use changes in the middle Fenhe River basin in Northern China. Issue 7 (10th June 2022) - Zhu, Xueping; Chang, Ke; Cai, Wenjun; Zhang, Aoran; Yue, Guangtao; Zhao, Xuehua
Abstract: Investigating and understanding the responses of runoff and nitrogen loading to climate and land use change is particularly important for future water resources management. In this article, the Soil and Water Assessment Tool (SWAT) was used to simulate runoff and nitrogen loading in the middle reaches of the Fenhe River. The model was calibrated by the SWAT calibration and uncertainty procedure (SWAT-CUP) to achieve the accuracy of simulating runoff and nitrogen loadings. Furthermore, 20 climate change scenarios and seven extreme land use change scenarios were set up and run on the calibrated model. The results showed that runoff and nitrogen loading decreased when temperature increased and increased with increasing precipitation. Runoff was more sensitive to changes in precipitation (±10%) than temperature (±2 °C), while nitrogen loading showed the opposite pattern. When the two climatic factors changed in the same direction, the combined effect was larger than either factor alone, whereas the change in the opposite direction produced a weaker effect. The changes produced by different extreme land use scenarios on runoff and nitrogen loading were significantly different and were more obvious during the flood season than in the non-flood season. The results of this study provide a useful guide for water resource managers. HIGHLIGHTS: Nitrogen loadings (including ammonia nitrogen and total nitrogen) and runoff were accurately simulated by the Soil and Water Assessment Tool (SWAT) with parameters calibrated by the SWAT calibration and uncertainty procedure (SWAT-CUP). Twenty climate change scenarios and seven extreme land use scenarios were simulated to determine effects on runoff and nitrogen loading using the calibrated SWAT model. Sensitivity of runoff and nitrogen loading to climate and land use changes was analyzed. Graphical Abstract